(untitled) (diségno, 2022)
The evocative venue of the Monumental Complex Real Belvedere of San Leucio in Caserta hosted, from the 11th to the 13th of May, the international conference Beyond All Limits promoted by the Department of Architecture and Industrial Design of the University ‘Luigi Vanvitelli’. Two prestigious foreign partner universities were involved, namely the Faculty of Architecture of Cankaya University in Ankara and the Department of Architecture and Engineering of the University of Strathclyde in Glasgow. [read more]